Hypoglycemic effect of Astragalus polysaccharide and its effect on PTP1B - WU Yong; OU-YANG Jing-ping; WU Ke; WANG Ya; ZHOU Yun-feng; WEN Chong-yuan (Acta Pharmacologica Sinica; Vol 26, No 3 (March 2005): Acta Pharmacologica Sinica, 2016)
Aim: To examine the effects of Astragalus polysaccharide (APS), a component of an aqueous extract of Astragalus membranaceus roots, on protein tyrosine phosphatase 1B (PTP1B), a negative regulator of insulin-receptor (IR) signal transduction, and its potential role in the amelioration of insulin resistance. Methods:Ten-week-old fat-fed streptozotocin (STZ)-treated rats, an animal model of type II diabetes mellitus (TIIDM), were treated with APS (400 mg/kg po) for 5 weeks. Insulin sensitivity was identified by the insulin-tolerance test. Further analyses on the possible changes in insulin signaling occurring in skeletal muscle and liver were performed by immunoprecipitation or Western blotting. PTP1B activity was measured by an assay kit. Results: The diabetic rats responded to APS with a significant decrease in body weight, plasma glucose, and improved insulin sensitivity. The activity and expression of PTP1B were elevated in the skeletal muscle and liver of TIIDM rats. Thus the insulin signaling in target tissues was diminished. APS reduced both PTP1B protein level and activity in the muscle, but not in the liver of TIIDM rats. Insulin-induced tyrosine phosphorylation of the IR β-subunit and insulin receptor substrate-1 (IRS-1) were increased in the muscle, but not in the liver of APS-treated TIIDM rats. There was no change in the activity or expression of PTP1B in APS-treated normal rats, and blood insulin levels did not change in TIIDM rats after treatment with APS. Conclusion: APS enables insulin-sensitizing and hypoglycemic activity at least in part by decreasing the elevated expression and activity of PTP1B in the skeletal muscles of TIIDM rats.